Stage-specific, strain-specific, and cross-reactive antigens of Leishmania species identified by monoclonal antibodies. - Handman, E (1982)
The fusion of NS-1 myeloma cells with spleen cells from mice chronically infected with Leishmania tropica resulted in nine clones of hybridomas producing monospecific antibodies to membrane antigens of L. tropica. One of the antibodies (L-5-85) bound specifically to the promastigote form of the parasite, and the remaining eight recognized antigens shared by the promastigote and amastigote of L. tropica. Four of the antibodies (L-5-16, L-5-34, L-5-44, and L-2-3F11) detected parasite antigens on the surface of L. tropica-infected macrophages. Common antigens shared by L. tropica, L. mexicana, and L. donovani were identified as well as one antigen apparent on most Leishmania spp. and present also in Crithidia fasciculata. Two monoclonal antibodies (L-5-27 and L-5-41) were found to bind only to strains of L. tropica from simple cutaneous leishmaniasis. A special property shared by these two antibodies was the inhibition of parasite growth in macrophages in vitro.